Search for Long-Lived Charged Massive Particles with the D0 Detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Neal, H. A.; et al. (Amer Physical Soc, 2009)
We search for long-lived charged massive particles using 1.1 fb(-1) of data collected by the D0 detector at the Fermilab Tevatron pp Collider. Time-of-flight information is used to search for pair produced long-lived tau sleptons, gauginolike charginos, and Higgsino-like charginos. We find no evidence of a signal and set 95% C.L. cross section upper limits for staus, which vary from 0.31 to 0.04 pb for stau masses between 60 and 300 GeV. We also set lower mass limits of 206 GeV (171 GeV) for pair produced charged gauginos (Higgsinos).